Immune checkpoint blockade induced shifts in cytokine expression patterns in peripheral blood of head and neck cancer patients are linked to outcome - Röhl, Louisa; Wellhausen, Jana; Berszin, Michael; Krücken, Irene; Zebralla, Veit; Pirlich, Markus; Wiegand, Susanne; Dietz, Andreas; Wald, Theresa; Wichmann, Gunnar (Frontiers in Immunology, 2023)
Compared to other malignancies including melanoma and various skin cancers with relatively high response rate above 50% and mostly long-lasting durable response to PD-1 immune checkpoint blockade (ICB), head and neck squamous cell carcinoma (HNSCC) belongs to another group of malignancies with lower response rate (5 to 40%) and increased frequency of relapse even after complete response (CR). Biomarkers to identify responders among HNSCC patients achieving CR curing the disease are urgently needed as the combined positive score of PD-L1 expression (CPS) and the tumor mutational burden (TMB) are far from perfect biomarkers for predicting CR to anti-PD-1 ICB. As anti-PD-1 ICB targets PD-1 expressed on natural killer (NK) and T cells, and their interaction with antigenpresenting cells (APC) but also tumor cells is orchestrated by cytokines, we analyzed cytokine expression patterns (CEP) in serum and plasma taken before and during PD-1 ICB and report about three prognostic subgroups of HNSCC identifiable by their CEP linked to significant different survival after PD-1 ICB.